Brand endorsements: An exploratory study into the effectiveness of using video game characters as brand endorsers - Shelton, J; Chiliya, N (My University, 2014)
Celebrity endorsements have been established as one of the most preferred methods of advertising by marketers (Patel, 2009). Biswas, Hussain and O’Donnell (2009) enumerates five specific benefits of employing celebrity endorsers for a brand, they can be summarised as follows: drawing attention, crisis management, brand repositioning, global marketing, and boosting sales. However the benefits of using a celebrity endorser can be markedly reversed if the celebrity, is involved in a controversial incident, loses credibility by endorsing too many brands, suddenly changes their image, overshadows the brand which is being endorsed, experiences a drop in popularity, is the centre of negative publicity, or fails to perform within their specific career (Erdogan, 1999). As a solution to these problems this research has investigated the use of video game characters as celebrity brand endorsers. Video game characters are celebrities in their own right but they are not plagued by the same risks and problems as ordinary celebrities (Avery, Ferrand, Nicholas & Rowley, 2006; Shimp & Till, 1998). This exploratory study used a quantitative research approach. A self-administered questionnaire using a 7-point Likert scale was developed and piloted. The questionnaire was distributed at the University of the Witwatersrand to a sample group of 484 respondents between the ages of 18 to 25. Fictitious adverts were used as stimuli during the questionnaire. Convenience sampling was used because of time and monetary constraints. The linear regression results proved that video game characters are effective as brand endorsers and can be used in place of an ordinary celebrity to increase the purchase intentions of the target audience. It can be recommended that video game companies seek opportunities to create partnerships with marketers to use their characters as brand endorsers.
Keywords: Brand Endorsement; Video Game Characters; Celebrities